Microstructure and Optimization of Sweet Potato-Rice Simulated Chips - Adil Basuki Ahza; Arief Munandar; Subarna Suryatman (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Optimization of formula, baking and frying condition, and microstructure of sweet potato - rice simulated chips were studied using a completely randomized factorial design based on its physical, chemical and sensorial characteristics. The formulas were enriched with a mixture of skim milk, carrots, celery and  temurui leaf powders to enhance its  functional properties. Parameters to measure chips quality include color, texture, moisture content, ash content, protein content, fat content, carbohydrate, and hedonic ratings of sensory analysis. The result showed that fried simulated chips tend to be more preferable compared to the baked simulated chips. Fried simulated chips were generally slightly darker than the baked chips. Both fried and baked simulated chips’ colors were dark yellow. The high temperature frying produced finer microstructure and massive gelatinization of the fried chips. The optimum formula and cooking process of simulated chip was obtained from sweet potato-rice simulated chips with ratio of 60:40 fried at 160°C for 1minute; and the sweet potato: rice with ratio of 80:20, baked at 180°C for 8 minutes. Best fried simulated chip color was dark yellow, with its brightness values(L) 46.77±0.00, yellowness value(a) +4.83±0.01, redness value(b) +34.40±0.06, hardness 827.77±43.78gf, moisture content 2.95 ± 0.28%(db), ash content 1.95±0.08%(db), protein content 3.07±0.13%(db), fat content 28.01±0.40%(db), and carbohydrate content 64.02±0.07%(db). Panelists tended to prefer the fried simulated chips with an overall score of 5.37±1.24c. While the best baked simulated chips color was dark yellow, with brightness values(L) 69.31±0.01, yellowness(a) +1.04±0.00, redness(b) +29.96±0.02, hardness  382.97±43.66gf,  moisture  content  2.37±0.76%(db),  ash  content  3.07±0.11%(db), protein    content    4.09±0.00%(db),    fat    content    1.67±0.25%(db)    and    carbohydrate 88.80±1.12%(db). Baked simulated chips tended to be neutrally acceptable with an overall rating of 4.34±1.35ab.